SYSTEM ANALYSIS AND SYNTHESIS IN INNOVATION GOVERNANCE: APPLICATION FOR THE ENERGY OF THE RUSSIAN FEDERATION - A. A. Nikonova (Real Economics Publishing House, 2014)
Introduces the concept of a planning methodology of innovation development of economic units and systems, as well as the enablers of innovation based both on system principles in governance and on the system views on guide directions for sustainable growth of the economic units and economy in a whole. The approach is an invariant to the examined object, further it’ll be considered for the Russian fuel and energy complex (FEC). Energy complex plays a fundamental role in the national economic system and is integrated deep in the world energy system, so the analysis of its current state and development of energy within the framework of the entire socio-economic system that most clearly shows the sources of resource superiority and slowing down innovation development of Russia. The estimates obtained are intended to make decisions in governance scientific based and to selection of efficient instruments to increase the innovation activity of both the energy units and the sys-tem as a whole.